2008
DOI: 10.1103/physreve.78.036204
|View full text |Cite
|
Sign up to set email alerts
|

Exotic orbits of two interacting wave sources

Abstract: As shown recently, it is possible to create, on a vibrating fluid interface, mobile emitters of Faraday waves [Y. Couder, S. Protière, E. Fort, and A. Boudaoud, Nature 437, 208 (2005)]. They are formed of droplets bouncing at a subharmonic frequency which couple to the surface waves they emit. The droplet and its wave form a spontaneously propagative structure called a "walker." In the present paper we investigate the large variety of orbital motions exhibited by two interacting walkers having different sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 19 publications
2
39
0
1
Order By: Relevance
“…In future work, one may apply the methodology of Durey and Milewski [26] followed here to the chaotic trajectories of walkers under the influence of a Coriolis force [12,23,39] with a view to seeking a similar double quantization in that system. A broader exploration of pilot-wave systems with different external forces and geometries should yield a better understanding of the emergent statistics of chaotic pilot-wave dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In future work, one may apply the methodology of Durey and Milewski [26] followed here to the chaotic trajectories of walkers under the influence of a Coriolis force [12,23,39] with a view to seeking a similar double quantization in that system. A broader exploration of pilot-wave systems with different external forces and geometries should yield a better understanding of the emergent statistics of chaotic pilot-wave dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments conducted over the past eight years have revealed that the resulting "path memory" is responsible for the complex walker dynamics and their quantum-like behavior [29]. Multiple walkers may interact with each other through their wave fields and thus exhibit interesting coherent behavior [26,28,55,30].…”
Section: Introductionmentioning
confidence: 99%
“…We proceed by investigating the interaction between a pair of walkers, as was examined experimentally by Protière et al (2006), Protière et al (2008) and Eddi et al (2012). We confine our attention to two special cases, where the walkers are initially antiparallel and parallel.…”
Section: Two-particle Interactionmentioning
confidence: 99%
“…We confine our attention to two special cases, where the walkers are initially antiparallel and parallel. Protière et al (2008) report that when the walkers are initially antiparallel, and so approach each other, they may either scatter or lock into orbit, depending on their relative bouncing phase, and the perpendicular distance between their original paths, the so-called impact parameter, d I .…”
Section: Two-particle Interactionmentioning
confidence: 99%